Assessment and Management of Hospital Acquired Infections in a Tertiary Care Hospital - Thomas, Divya; Nair, Sujith S; P, Kavyanjana; KP, Saleed; KP, Shahir (Indian Journal of Pharmacy Practice)
Aim: To assess hospital acquired infections and its management in a tertiary care hospital. Materials and Methods: A cross-sectional study of six months was carried out. Utilizing SPSS Version 25 and Microsoft Office Excel, statistical analysis was carried out, after the collected data were imported into Excel. Results: In our investigation, the prevalence of hospital acquired infections was discovered to be 6.1%. Male patients made up 70% of study’s total participants while female made up 30%. The highest distribution of Hospital Acquired Infections (HAI) was found to be Bloodstream Infection (BSI) (41.80%), followed by Hospital-Acquired Pneumonia (HAP) (17.20%), Respiratory tract infections (RTI) (13.90%) and other HAI. (Hospital Aquired Infections). Most common causative organism was found to be as Klebsiella pneumoniae (15.46%). According to lab investigations, Leukocytosis (61.47%), Neutrophilia (59.83%), Lymphopenia (78.68%), Hyperglycaemia (53.3%) and elevated level of CRP (81.13%) was found in majority patients. Most of the patients were treated with Meropenem (17.55%), Linezolid (15.98%) and others. Conclusion: Hospital acquired infections are a significant risk to medical facilities and one of the most often avoidable negative patient outcomes. They make a major contribution to hospital expenses and mortality rates. The basis of effective infection control programmes in hospitals can be the monitoring of antibiotic resistance in conjunction with tracking physician prescribing patterns.
Keywords: Hospital Acquired Infections (HAI); Nosocomial infections; Causative organism; Prevalence